Comparison of efficacy between 128-slice MDCT colonography and conventional colonoscopy in detecting colorectal polypoid lesions - Iskandar, Nur Hazrina (2017)
Objectives: To determine the efficacy and agreement between 128-slice MDCT colonography (CTC) in characterise the colorectal polyp mucosal lesions based on size, location and morphology in comparison with conventional colonoscopy (CC). Methodology: A cross-sectional study was conducted from July 2013 till June 2016 in Department of Radiology and Endoscopy Unit, Department of Surgery, Hospital Universiti Sains Malaysia (USM). Seventy five subjects who were symptomatic for colorectal carcinoma and clinically indicated for CC were included. Ethical approval obtained from The Human Research Ethics Committee of USM (JEPeM). Image acquisition obtained by using 128-slice CT scan and image analysis performed using PACS and VitreaCore (version 6.7.2020). They ranged in age from 22 to 82 years with mean age of 56.1±16.0 years old. Majority of subjects are male (65.3%) with male to female ratio of 2:1 and Malays (81.4%). Results: Only 46 subjects had positive colorectal polyp lesions and 29 subjects had normal findings on both CTC and CC. A total of 294 lesions were detected on CTC, only 162 lesions detected in both CTC and CC. However, 132 lesions were not detectable on CC as false positive. CTC showed a high percentage of detection based on the size of the colorectal polyp lesions as compared to CC. For lesions with size in between 5 to 9 mm the percentage of detection in CTC and CC were 37.1% and 2.4%. The percentage of detection for lesion size more than 9 mm in both CTC and CC were 40.8% and 32.0%, respectively. However, equal percentage of detection of lesion size less than 5 mm which were 22.1% and 20.7%, respectively. For the segmental localization, CC was detected ahigher number of polyp lesions in the rectum, 10.9%. However, in CTC most of the colonic polyp lesions were detected in the ascending colon and rectum which accounted 17.7% for each segment. The percentage of detection of lesion morphology was higher in CTC as compared to CC. All the detected colorectal polyp lesions in CTC were soft tissue attenuation based on in Hounsfield Units. In this study, the degree of agreement between CTC and CC examinations were proven by Cohen’s kappa statistic (kappa agreement analysis) in determining the size, locations and morphology of colorectal polyp lesions. There was significant moderate agreement (kappa value of 0.431) in determination of the lesion size for CTC and CC. In CTC, increase in percentage of detection for colonic polyp lesions more than 9 mm. There was significant almost perfect agreement between findings by CTC and CC in determination of the lesion’s morphology and location with kappa value of 0.990 and 1.000, respectively (McHugh, 2012). Conclusion: CT colonography has a better performance and is ahead in front of CC in the detection and characterization of the colorectal polyp lesions based on size, location, and morphology. However, both CTC and CC were considered as backbone and prime modality that complementing each other in detection of the colorectal polyp lesions.